EFFORTS OF PAIDBP TEACHERS TO IMPROVING STUDENT LEARNING MOTIVATION AT UPTD SDN KAMAL 2 - Wilda Maulidiyah Saniyah; Conny Dian Sumadi; Sunarni (maktab: Jurnal Pendidikan dan Teknologi, 2022)
This article discusses field research that has been conducted regarding the efforts of Islamic Religious Education and Moral Education (PAIdBP) subject teachers to increase students' learning motivation so that learning achievement can increase. This research was conducted because of the importance of learning motivation possessed by students in the learning process in order to get learning achievements in accordance with learning objectives. The purpose of this study was to find out the efforts made by PAIdBP teachers in improving student achievement. The data in this study were obtained from observations, interviews and documentation. Observations and documentation were carried out during class lessons, while interviews were conducted outside the classroom with religion teachers at SDN Kamal 2. The results of the study show that teachers apply various efforts to increase students' learning motivation. Learning motivation needs to be improved so that the learning achievement of students can increase. This research should be a reference for improving student learning achievement by making efforts to arouse and increase student learning motivation so that learning achievement increases through PAIdBP lessons.